Enhanced luminescence/photodetecting bifunctional devices based on ZnO:Ga microwire/p-Si heterojunction by incorporating Ag nanowires. Issue 19 (25th August 2021) - Liu, Yang; Dai, Ruiming; Jiang, Mingming; Tang, Kai; Wan, Peng; Kan, Caixia
Abstract : A fabricated n-AgNWs@ZnO:Ga microwire/p-Si heterojunction is used to achieve high-performance light-emitting/detecting bifunctional devices. Abstract : With the disadvantages of indirect band gap, low carrier mobility, and large lattice mismatch with other semiconductor materials, one of the current challenges in Si-based materials and structures is to prepare low-dimensional high-performance optoelectronic devices. In this work, an individual ZnO microwire via Ga-incorproration (ZnO:Ga MW) was employed to prepare a light-emitting/detecting bifunctional heterojunction structure, combined with p-type Si crystal wafer as a hole transporting layer. In a forward-bias regime, red luminescence peaking at around 680 nm was captured. While, the fabricated heterojunction device also exhibited an obvious photoresponse in the ultraviolet wavelengths. Interestingly, the introduction of Ag nanowires (AgNWs) are utilized to increase light output with amplitude 4 times higher than with that of naked wire-based LEDs. Similarly, the performance parameters of the fabricated n-AgNWs@ZnO:Ga MW/p-Si heterojunction photodetector are significantly enhanced, containing a responsivity of 5.52 A W −1, detectivity of 2.34 × 10 12 Jones, external quantum efficiency of 1.9 × 10 3 % illuminated under 370 nm at −1 V. We compare this work with previous reported photodetectors based on various ZnO/Si-based materials and structures, some performance parameters are not superior, but our constructed n-AgNWs@ZnO:Ga MW/p-Si heterojunction photodetector has comparable overall characteristics, and our findings stand out especially for providing an inexpensive and suitable pathway for developing low-cost, miniaturized and integrated ultraviolet photodetectors. The demonstration of AgNWs enhanced low-dimensional light-emitting/detecting bifunctional photodiodes can offer a promising scheme to construct high-performance Si-based optoelectronic devices.